2016
DOI: 10.1186/s12913-016-1303-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to breast cancer detection mode and time to diagnosis in Alberta, Canada: a population-based retrospective cohort study

Abstract: BackgroundUnderstanding the factors affecting the mode and timeliness of breast cancer diagnosis is important to optimizing patient experiences and outcomes. The purposes of the study were to identify factors related to the length of the diagnostic interval and assess how they vary by mode of diagnosis: screen or symptom detection.MethodsAll female residents of Alberta diagnosed with first primary breast cancer in years 2004–2010 were identified from the Alberta Cancer Registry. Data were linked to Physician C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Of these 19, 11 had a median diagnostic interval 24 months after a negative screening mammogram (known as interval cancers). 29 The only other Canadian evidence on the breast cancer screening detection rate comes from two recent studies in Alberta, with one reporting that 44% of all breast cancers were detected through screening from 2007 to 2010 24 and the other reporting a screening detection rate of 38% from 2004 to 2010 25 (we observed 36% in Ontario in 2011). Screening eligibility criteria differ between the two provinces, as the Alberta Breast Cancer Screening Program additionally accepts patients aged 40 to 49 years.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Of these 19, 11 had a median diagnostic interval 24 months after a negative screening mammogram (known as interval cancers). 29 The only other Canadian evidence on the breast cancer screening detection rate comes from two recent studies in Alberta, with one reporting that 44% of all breast cancers were detected through screening from 2007 to 2010 24 and the other reporting a screening detection rate of 38% from 2004 to 2010 25 (we observed 36% in Ontario in 2011). Screening eligibility criteria differ between the two provinces, as the Alberta Breast Cancer Screening Program additionally accepts patients aged 40 to 49 years.…”
Section: Resultsmentioning
confidence: 84%
“…Our observations differed from findings in Alberta, which reported medians of 19 days for the screen-detected patients and 21 days for the symptomatic patients in the years 2004 to 2010. 25 Within Ontario, we observed significant regional variation in the diagnostic interval. The maximum difference was 2.4 weeks (17 days) between LHINs.…”
Section: Strengths and Limitationsmentioning
confidence: 76%
See 1 more Smart Citation
“…Yet, even in countries with free access to health care, women are still diagnosed via breast symptoms instead of screen detected and there is variance in time to diagnosis. Authors attributed differences to variation in care coordination particularly in areas with lack of medical resources and rural areas (Yuan et al, 2016). In contrast, this study showed the reasons for delays may be related to interpersonal factors between patient and provider.…”
Section: Discussionmentioning
confidence: 99%
“…A number of researchers have reported associations between longer intervals and later stages of cancer at diagnosis, reduced survival, decreased quality of life post-treatment, and suboptimal patient experience [3,6]. In Alberta, analyses of administrative data spanning 2004-2011 described potentially preventable long periods from suspicion to diagnosis for breast, colorectal, and lung cancers [7][8][9][10]. In Canada and across the world there are substantial variations in the length of the diagnostic period for different cancers [4,11], and numerous studies have focused on understanding factors that may influence this timeline in order to improve health outcomes and patient experience [12].…”
Section: Introductionmentioning
confidence: 99%